Pengaruh Iklan Dan Kualitas Produk Terhadap Keputusan Pembelian Mie Lemonilo - Ageng Saepudin Kanda; Nanda Fitria Auntari (STIKes Ibnu Sina Ajibarang, 2024)
This article aims to determine the influence of advertising and product quality on purchasing decisions. With increasing market competition in selling instant noodles in Indonesia, business people must strengthen marketing methods and promotional strategies and create products with good quality and quality in order to achieve maximum sales targets. The marketing technique used in this research is to use advertising to disseminate information about the products being sold. The Lemonilo company also uses advertising by collaborating and using brand ambassadors to introduce the products it produces. So that people can get to know healthy food and change healthy food patterns by getting to know Lemonilo products.